2002
DOI: 10.1007/s00421-002-0704-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disparity change on binocular visual evoked potential parameters elicited by convergent dynamic random-dot stereogram stimuli in humans

Abstract: Binocular visual evoked potentials (VEP) were recorded from the left and right occipital cortices of right-handed subjects in response to six different levels of convergent disparity using the stimulus of dynamic random-dot stereogram (DRDS). The VEP obtained consisted of a negative (N1) and a positive peak (P1) within intervals of 200-400 ms and 400-600 ms, respectively. The latency of the N1 wave decreased with disparity and the amplitude of the same wave displayed a concave-down curve. The tuning-curve of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Sahinoglu et al in 2002 used dynamic RD stereogram presentations with convergent disparities to identify an N1 peak (200-400 ms) whose peak latency and amplitude changed with increasing disparity. 32 Many other studies also have reported a similar effect on the early negativity. [33][34][35][36][37][38][39] In our current study, an enhanced N1 peak was observed in response to the HD condition, which appeared as a surface corrugated in depth, compared to the ZD condition, which was a fusible flat surface.…”
Section: Evoked Potentials To Static Pattern Onset Stimulationmentioning
confidence: 63%
“…Sahinoglu et al in 2002 used dynamic RD stereogram presentations with convergent disparities to identify an N1 peak (200-400 ms) whose peak latency and amplitude changed with increasing disparity. 32 Many other studies also have reported a similar effect on the early negativity. [33][34][35][36][37][38][39] In our current study, an enhanced N1 peak was observed in response to the HD condition, which appeared as a surface corrugated in depth, compared to the ZD condition, which was a fusible flat surface.…”
Section: Evoked Potentials To Static Pattern Onset Stimulationmentioning
confidence: 63%
“…Every dot contained 6 × 6 pixels and the duty ratio of the dots was 50%. Because the dynamic RDS would induce the continuous snowstorm (dynamic TV noise) and lead to much sense of flash, an altered approach was used to remove the monocular cues in the image sequence 21 39 . A square of 660 × 660 pixels was designed, which was large enough for containing the digits or fixation cross and was at the center of each image.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies show that after watching a period of 3D movies the accumulative visual fatigue could cause changes of EEG-related signals, such as the energy in certain wavebands 18 , the steady-state evoked potential (SSVEP) or the P600 (a delayed member of the P3 component) 19 . For real-time measurements, some studies have found that small horizontal disparities did have influences on early event-related potential (ERP) components 20 21 22 23 24 , such as P1 20 , N1 23 24 , P2 24 and N2 23 . The later ERP components, however, have been less investigated when watching the comfortable 3D images.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Random‐dot stereograms (RDS) and dynamic random‐dot stereograms (DRDS) with various horizontal disparities are often used as stimuli to evoke depth‐related VEPs. In previous literature, results show differences in the latencies and in the number of peaks recorded 6–18 . Most investigators have obtained a prominent negative peak with a latency of 100 to 300 ms, which has been considered as sensitive to the disparity of stimulus.…”
Section: Introductionmentioning
confidence: 94%